The Derived Allele of ASPM Is Associated with Lexical Tone Perception - Wong, Patrick C. M. (Public Library of Science, 2012)
The ASPM and MCPH1 genes have been implicated in the adaptive evolution of the human brain [Mekel-Bobrov N. et al., 2005. Ongoing adaptive evolution of ASPM, a brain size determinant in homo sapiens. Science 309; Evans P.D. et al., 2005. Microcephalin, a gene regulating brain size, continues to evolve adaptively in humans. Science 309]. Curiously, experimental attempts have failed to connect the implicated SNPs in these genes with higher-level brain functions. These results stand in contrast with a population-level study linking the population frequency of their alleles with the tendency to use lexical tones in a language [Dediu D., Ladd D.R., 2007. Linguistic tone is related to the population frequency of the adaptive haplogroups of two brain size genes, ASPM and microcephalin. Proc. Natl. Acad. Sci. U.S.A. 104]. In the present study, we found a significant correlation between the load of the derived alleles of ASPM and tone perception in a group of European Americans who did not speak a tone language. Moreover, preliminary results showed a significant correlation between ASPM load and hemodynamic responses to lexical tones in the auditory cortex, and such correlation remained after phonemic awareness, auditory working memory, and non-verbal IQ were controlled. As in previous studies, no significant correlation between ASPM and cognitive measures were found. MCPH1 did not correlate with any measures. These results suggest that the association between the recently derived allele of ASPM is likely to be specific and is tied to higher level brain functions in the temporal cortex related to human communication.